Foreign Capital, Inflation, Sterilization, Crowding-Out and Growth: Some Illustrative Models - Nirvikar Singh; T. N. Srinivasan (University of California, Economics Department, 2004)
This paper discusses some puzzles in the contemporary macroeconomic scene in India, from the perspective of public finance and economic development. These include a fiscal deficit higher than it was during the 1991 crisis, but without a large current account deficit or rise in inflation or interest rates, a rising inflow of external capital, accompanied by the RBI's sterilizing these inflows and accumulating large reserves, even in the face of low inflation. We offer a critique of some previous analyses, and some models that are suggestive of how real and monetary factors might be integrated in providing a firmer grounding for the policy debates current in India.
Keywords: 330; foreign capital; sterilization; absorption; crowding out; inflation; growth